Takhrij and Syarah Hadith of Chemistry: Benefits and Role of Honey as a Medicine Material - Muhamad Sahlan Arrosyid; Nurkholish Hadi; Ahmad Izzan; Rifki Rosyad; Eko Prabowo Hadisantoso (UIN Sunan Gunung Djati Bandung, 2021)
The purpose of this hadith is to discuss the hadith of the Prophet (ï·º) about the benefits of honey from a chemical perspective. This research method is qualitative through the approach of takhrij and sharah hadith with chemical analysis. The results and discussion of this study is that honey contains many chemical substances that are beneficial to health and their uses in the world of medicine. The conclusion of this research is takhrij and syarah hadith of the Prophet (ï·º) about honey by chemical analysis has benefits for health and treatment.